Colocar-se em palavras: memórias de um percurso íntimo - Regina Dalcastagnè (Estudos de Literatura Brasileira Contemporânea)
Based on a rapprochement between the award-winning novel Nur na escuridão (Nur in darkness), by Salim Miguel, which tells his family’s saga during his immi- gration from Lebanon to Brazil, and the unpublished manuscripts of Jose Miguel, the author’s father, who tells the same story, this article discusses the reasons for writing and the use of narrative resources to build a meaning for his life. Amid the text of a legitimate writer and the one of an old grocer who wrote in Arabic and has hidden his notebook to death, there is a common will to truth, although the results may be different, with emphasis either to the “typical” character of the experience or to what it has of “singular”.